On the Return of the (Media) Author: Michel Houellebecq, écrivain médiatique - Harris, Ashley (My University, 2020)
This article argues that Michel Houellebecq is an écrivain médiatique, a media author, and examines how and why he engages in a type of authorial strategy that relies on more than the text and presents the author as a multimedia, visible and culturally relevant figure. It will address how Houellebecq attempts to situate and justify this media-focused and author-centric strategy, showing how this reflects a broader sociocultural shift. The article will first deal with the concept of media authorship, defining and situating it, to show how Houellebecq can productively be understood as an écrivain médiatique. The type of authorship that Houellebecq represents through use of more than the text but media activities and opportunities for visibility presents us with an epistemological need to reassess literary authorship in the media age. This article engages with critical tools that are able to address new authorial strategies. Firstly, this article will address Jérôme Meizoz’s concept of posturing (2007) as a productive lens through which to understand Houellebecq's polemical public persona as it oscillates in and out of his novels. In doing so, the article considers how his posturing indicates a reliance on visibility for success in the contemporary sociocultural context. Secondly, the article examines the range of Houellebecq’s multimedia activities and creations beyond the text, including adaptations, albums, exhibitions, films, photography, and media appearances, decentring the text as part of a broader transmedial whole, using Richard Saint-Gelais’ concept of transmediality (2011). This will show how Houellebecq is producing a multimedia world beyond the text and constructing himself as more than an author. Finally, this article discusses the evocation of social discourse, to use Marc Angenot’s term (1989), in Houellebecq’s works as a means to present a digital and mass media orientated cultural context in order to justify and rationalise his media-focused acts. These tools provide a framework that enables us to better evidence and understand Houellebecq’s focus beyond the text. This strategy for successful authorship, reliant on mediatisation and multimedia, reflects the challenges of the cultural domination of mass media and new technologies of the Digital Age and indicates that the autonomy of the literary field is diminishing as it comes under the increased influence of industry, and other media forms and cultural fields. This article will show how a superficially transgressive engagement with the media and multimedia in fact reflects consent to the dynamics and values of the contemporary sociocultural context.
Keywords: Creative Arts Practice; Digital Humanities; Identities in Transformation; Manuscript, Book and Print Cultures